ChatGPT usage and attitudes are driven by perceptions of usefulness, ease of use, risks, and psycho-social impact: a study among university students in the UAE - Sallam, Malik; Elsayed, Walid; Al-Shorbagy, Muhammad; Barakat, Muna; El Khatib, Sami; Ghach, Wissam; Alwan, Nisreen; Hallit, Souheil; Malaeb, Diana (Frontiers in Education, 2024)
Background: The use of ChatGPT among university students has gained a recent popularity. The current study aimed to assess the factors driving the attitude and usage of ChatGPT as an example of generative artificial intelligence (genAI) among university students in the United Arab Emirates (UAE). Methods: This cross-sectional study was based on a previously validated Technology Acceptance Model (TAM)-based survey instrument termed TAME-ChatGPT. The self-administered e-survey was distributed by emails for students enrolled in UAE universities during September–December 2023 using a convenience-based approach. Assessment of the demographic and academic variables, and the TAME-ChatGPT constructs’ roles in ChatGPT attitude and usage was conducted using univariate followed by multivariate analyses. Results: The final study sample comprised 608 participants, 91.0% of whom heard of ChatGPT while 85.4% used ChatGPT before the study. Univariate analysis indicated that a positive attitude to ChatGPT was associated with the three TAME-ChatGPT attitude constructs namely, lower perceived risks, lower anxiety, and higher scores on the attitude to technology/social influence. For the ChatGPT usage, univariate analysis indicated that positive attitude to ChatGPT use was associated with being male, Arab in nationality, and lower point grade average (GPA) as well as the four ChatGPT usage constructs namely, higher perceived usefulness, lower perceived risks of use, higher scores on the behavior/cognitive construct and higher scores on the ease-of-use construct. In multivariate analysis, only TAME-ChatGPT constructs explained the variance in attitude towards ChatGPT (80.8%) and its usage (76.9%). Conclusions: The findings indicated that ChatGPT usage is commonplace among university students in the UAE. The determinants of use included the perceived usefulness, lower perceived risks, cognitive and behavioral factors, perceived ease of use, while the attitude was determined by lower perceived risks, lower anxiety, and higher scores for attitude to technology/social influence. These factors should be considered for understanding the motivators for successful adoption of genAI including ChatGPT in higher education.